2018
DOI: 10.3390/jpm8040045
|View full text |Cite
|
Sign up to set email alerts
|

DPYD, TYMS and MTHFR Genes Polymorphism Frequencies in a Series of Turkish Colorectal Cancer Patients

Abstract: Fluoropyrimidine-based chemotherapy is extensively used for the treatment of solid cancers, including colorectal cancer. However, fluoropyrimidine-driven toxicities are a major problem in the management of the disease. The grade and type of the toxicities depend on demographic factors, but substantial inter-individual variation in fluoropyrimidine-related toxicity is partly explained by genetic factors. The aim of this study was to investigate the effect of dihydropyrimidine dehydrogenase (DPYD), thymidylate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
13
1
1
Order By: Relevance
“… NA Bacillus; Staphylococcus; Mycobacterium ( Jäckh et al., 2012 ) 12 Methyl red or azo dye a Textile dyes, tattoo inks, and cosmetic colorant Acting on other nitrogenous compounds as donors Acting on the CH-CH group of donors; acting on other nitrogenous compounds as donors; acting on single donors with incorporation of molecular oxygen (oxygenases); acting on paired donors, with incorporation or reduction of molecular oxygen Azoreductase (Azo1) FMN-dependent NADPH azoreductase (Azo1); NAD(P)H-dependent oxidoreductase; 4-(dimethylamino) phenylazoxybenzene reductase; azobenzene reductase Staphylococcus; Corynebacterium; Micrococcus; Dermacoccus; Kocuria Staphylococcus; Bacillus ( Stingley et al., 2010 ) 13 Fluorouracil Used in actinic keratosis and skin warts conditions Glycosyltransferases; acting on the CH-CH group of donors Glycosyltransferase; acting on the CH-CH group of donors; acting on paired donors, with incorporation or reduction of molecular oxygen; acting on CH or CH 2 groups; glycosylases; acting on carbon-nitrogen bonds, other than peptide bonds Orotate phosphoribosyl transferase; uridine phosphorylase; thymidine phosphorylase; dihydropyrimidine dehydrogenase Orotate phosphoribosy ltransferase; uridine phosphorylase; thymidine phosphorylase; dihydropyrimidine dehydrogenase; unspecific monooxygenase NA Yersinia; Wolinella; Vibrio; Tolumonas; Shigella; Aeromonas; Xylella ; etc. ( Amirfallah et al., 2018 ; Longley et al., 2003 ) 14 Propylene glycol Used as demulcent and in skin lotions and ointments Acting on the CH-OH group of donors Acting on the CH-OH group of donors; carbon-carbon lyases; carbon-oxygen lyases Alcohol dehydrogenases L-glycol dehydrogenase; aldehyde reductase; glycerol dehydrogenase; lactaldehyde reductase; propanediol dehydratase; etc. NA Salmonella; Escherichia; Geobacillus; Citrobacter; Klebsiella ; etc.…”
Section: Resultsmentioning
confidence: 99%
“… NA Bacillus; Staphylococcus; Mycobacterium ( Jäckh et al., 2012 ) 12 Methyl red or azo dye a Textile dyes, tattoo inks, and cosmetic colorant Acting on other nitrogenous compounds as donors Acting on the CH-CH group of donors; acting on other nitrogenous compounds as donors; acting on single donors with incorporation of molecular oxygen (oxygenases); acting on paired donors, with incorporation or reduction of molecular oxygen Azoreductase (Azo1) FMN-dependent NADPH azoreductase (Azo1); NAD(P)H-dependent oxidoreductase; 4-(dimethylamino) phenylazoxybenzene reductase; azobenzene reductase Staphylococcus; Corynebacterium; Micrococcus; Dermacoccus; Kocuria Staphylococcus; Bacillus ( Stingley et al., 2010 ) 13 Fluorouracil Used in actinic keratosis and skin warts conditions Glycosyltransferases; acting on the CH-CH group of donors Glycosyltransferase; acting on the CH-CH group of donors; acting on paired donors, with incorporation or reduction of molecular oxygen; acting on CH or CH 2 groups; glycosylases; acting on carbon-nitrogen bonds, other than peptide bonds Orotate phosphoribosyl transferase; uridine phosphorylase; thymidine phosphorylase; dihydropyrimidine dehydrogenase Orotate phosphoribosy ltransferase; uridine phosphorylase; thymidine phosphorylase; dihydropyrimidine dehydrogenase; unspecific monooxygenase NA Yersinia; Wolinella; Vibrio; Tolumonas; Shigella; Aeromonas; Xylella ; etc. ( Amirfallah et al., 2018 ; Longley et al., 2003 ) 14 Propylene glycol Used as demulcent and in skin lotions and ointments Acting on the CH-OH group of donors Acting on the CH-OH group of donors; carbon-carbon lyases; carbon-oxygen lyases Alcohol dehydrogenases L-glycol dehydrogenase; aldehyde reductase; glycerol dehydrogenase; lactaldehyde reductase; propanediol dehydratase; etc. NA Salmonella; Escherichia; Geobacillus; Citrobacter; Klebsiella ; etc.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, several other studies suggest different points of view. Maarten [ 26 ], Amirfallah [ 27 ], and McLeod et al [ 28 ] revealed that DPYD heterozygous for 85T>C was not associated with a decreased risk for grade 3 to 4 toxicity. In our study cohort, we haven't found a statistically significant relationship between DPYD*2A, *5A, *9A polymorphism and severe chemotherapy-related toxicity, owing to the limited size of the cohort in our study, and different allele frequency of these gene variants among different populations in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant association was found between DPYD, TYMS polymorphisms and fluoropyramidine-driven toxicities. Authors suggest that MTHFR polymorphisms may be regarded as related factors of fluoropyrimidine toxicity and can be used as predictive biomarkers for patients with CRC who can receive the greatest benefit from fluoropyrimidine-based regimens [40].…”
Section: Interaction Of Multiple Genes On Treatment Responsementioning
confidence: 99%